A Classroom Listening Teaching Practice - Razali Abdullah; Rika Ariska; Lia Rezita; Siti Nurhaliza; Hidayat Hidayat (Universitas Serambi Mekkah, 2020)
The aims of this study were (1) to find out how the teachers of SMP Negeri 5 Banda Aceh prepare teaching and learning process on listening instruction. (2) to find out how the teachers of SMP Negeri 5 Banda Aceh conduct teaching and learning process of listening instruction. And (3) to find out how the teachers of SMP Negeri 5 Banda Aceh evaluate the result on teaching and learning process of listening instruction. The subject of this study was the teachers of SMP Negeri 5 Banda Aceh who teach English. The number subjects are two teachers. The method used was descriptive analysis. Required data were collected through observation and interview. The data were analyzed by narration procedure and discussing. The result shows that before teaching and learning process was conducted, the teachers prepared teaching administrative requirement such as lesson plan based on the syllabus. The schedule and time allocation were suited with annual program, terms, and duration of effective week. During the teaching process, the teachers used four techniques of teaching listening skills namely: listening to dialogue, listening to a song, listening to the story that the teacher read and discussed. In teaching and listening process of listening instruction, the teacher applied Learner-Centered Approach. Next, the teachers evaluated students in two kinds of tests namely ongoing process test and final test.